Liberal Internationalism, Offensive Realism and Intelligence Liaison: The Case of the Israeli and South African Intelligence Services - Swart, Marno; Coetzee, Eben (Scientia Militaria - South African Journal of Military Studies, 2023)
For better or worse, the study of International Relations (IR) continues to be marked by a protracted battle between two competing theories: realism and liberal internationalism. This article seeks to investigate which theory, offensive realism or liberal internationalism offers a more compelling explanation for the alliance formation of the intelligence services of Israel and South Africa. Although scholars have indeed examined the explanatory merit of realism and liberal internationalism in explaining the foreign policy behaviour of (liberal) democratic and mixed (democratic and non-democratic) dyads, attempts at bringing the two theories to bear on the interactions of intelligence services have not been forthcoming, a shortcoming this article attempts to address. This article seeks to bridge this gap by evaluating the relative explanatory worth of offensive realism and liberal internationalism in accounting for the alliance formation of the intelligence services of Israel and South Africa. The significance of this article lies in its examination of international politics and realist thought through the specific lens of intelligence services.